Penerapan Media Audiovisual pada Pembelajaran Mufrodat Siswa Kelas IX Madrasah Tsanawiyah Ma’had Tahfidz Izzah Zamzam Surakarta Tahun Ajaran 2023/2024 - Muhammad Bahrul Hanan (Thulabuna: Jurnal Pendidikan Bahasa Arab, 2023)
This study discusses the Application of Audiovisual Media in Vocabulary (Mufrodat) Learning for Ninth-Grade Students at Madrasah Tsanawiyah Ma’had Tahfidz Izzah Zamzam Surakarta in the 2023/2024 Academic Year. At Ma’had Tahfidz Izzah Zamzam Surakarta, the teaching of mufrodat has still been using the lecture method, which causes students to be less active and negatively affects their achievement scores. The focus of this study is to: Investigate the application of audiovisual media in daily mufrodat learning for ninth-grade students at Madrasah Tsanawiyah Ma’had Tahfidz Izzah Zamzam Surakarta. Determine the results of applying audiovisual media in mufrodat learning for ninth-grade students at the same institution. Identify the supporting and inhibiting factors related to the use of audiovisual media in mufrodat learning for ninth-grade students at Madrasah Tsanawiyah Ma’had Tahfidz Izzah Zamzam Surakarta. The research method used in this study is Classroom Action Research (CAR), employing the Kemmis and McTaggart model, with the use of audiovisual media. The implementation structure includes the following steps: the teacher writes the material on the board, and the students copy it. The teacher reads aloud what is written, and the students imitate. Then, the teacher plays a video while pressing the Play/Pause button every five videos until all the targeted mufrodat are delivered. This study consists of two cycles. In the pre-cycle, 30% of students achieved mastery with an average class score of 60. In the first cycle, 30% of students achieved mastery with an average score of 64.5. In the second cycle, 100% of students achieved mastery with an average class score of 88. Conclusion: The final data show that the application of audiovisual media has a positive impact on improving students’ scores. The researcher concludes that vocabulary (mufrodat) learning using audiovisual media can increase students’ activeness, enthusiasm, and academic achievement.